2017
DOI: 10.1111/medu.13387
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of simulated patients on health care learners’ communication skills: a systematic review

Abstract: SP-based education is widely accepted as a valuable and effective means of teaching communication skills but there is limited evidence of how this translates to patient outcomes and no indication of economic benefit for this type of training over another method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
101
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(107 citation statements)
references
References 70 publications
0
101
0
6
Order By: Relevance
“…This enhances the likelihood that the students will suspend disbelief, perceive the situation to be realistic, and engage accordingly (Kaplonyi et al, 2017). Simulated patients allow practice at developing skills in interpersonal interactions, including interview skills (Kaplonyi et al, 2017;Sabus & Macauley, 2016). Simulated patient methodology is used in the CF-SCP to enhance the authenticity of interactions between students, clients, and stakeholders (Herrington & Oliver, 2000;Nestel, Sanko, & McNaughton, 2018;Rodger et al, 2010).…”
Section: Simulated Patients and Key Stakeholdersmentioning
confidence: 99%
“…This enhances the likelihood that the students will suspend disbelief, perceive the situation to be realistic, and engage accordingly (Kaplonyi et al, 2017). Simulated patients allow practice at developing skills in interpersonal interactions, including interview skills (Kaplonyi et al, 2017;Sabus & Macauley, 2016). Simulated patient methodology is used in the CF-SCP to enhance the authenticity of interactions between students, clients, and stakeholders (Herrington & Oliver, 2000;Nestel, Sanko, & McNaughton, 2018;Rodger et al, 2010).…”
Section: Simulated Patients and Key Stakeholdersmentioning
confidence: 99%
“…Some systematic reviews report studies of particular pedagogical methods , such as debriefing approaches, roles for observers or instructional design features . Other systematic reviews investigate how simulation supports learning in particular topics , such as empathy, communication skills or clinical reasoning skills . Likewise, literature reviews describe studies of modalities such as simulated patients and virtual patients .…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with previous studies in the same field. In a recent systematic review (119), the impact of simulated patients on communication skills in health care was studied. The authors concluded that simulation training is valua-ble and effective for teaching communication skills.…”
Section: Learning To Communicatementioning
confidence: 99%